Developing a Human-Centered Design Model of Disaster Management - Thomas Triadi Putranto, Novie Susanto (2016)
ABSTRACT The occurrence of natural disasters include landslides are part of the human life that can not be suspected. Knowledge and education regarding the disasters is absolutely required by the people in the disaster areas to achieve a safe, responsive and resilient state in disaster management. Based on the fact that Semarang city has a quite high potential of landslides occurrence in its almost area, human factors should be deeply considered since human is the most influenced part of the system if the disaster occurs and human also suspected as one of the cause of disaster occurance. Empowerment of human as individual and community is an important point to achieve a successful of disaster management program. Community preparedness in disaster management can be mapped through a questionnaire-based interviews to obtain behavior of community in landslides preventing, facing and coping. So this study aims at developing model of a human-centered design in disaster management especially in landslide cases in Semarang city using human factor toolkits. This also aims at obtaining a detailed phase of disaster management with focusing on community awareness both of in cognitively and physically states.